ENHANCING ENGLISH LEARNING WITH QUIZIZZ: A REVIEW OF STUDENTS' PERSPECTIVES - Rizky Ayuk Juvanichasari; Yoyok Andriyanto; Wiyaka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Abstract. This article presents a comprehensive review of the effectiveness of Quizizz as an online learning platform for teaching English, with a focus on students' perceptions. The integration of technology in English language education has become increasingly important, and Quizizz has gained popularity as a tool for enhancing reading and vocabulary skills. The study examines the impact of Quizizz on various aspects of the learning process, including interest, understanding, interactivity, collaboration, motivation, critical thinking, error improvement, and exam preparedness. Through the analysis of selected articles, this review provides valuable insights and perspectives on the application of Quizizz in English language education. Keywords: Quizizz, online learning platform, English language teaching, student perceptions, effectiveness.